STUDI INVESTASI PENINGKATAN JALAN PADA RUAS KELAY – LABANAN, LABANAN – TANJUNG REDEB, TANJUNG REDEB – BATAS BULUNGAN - NARDI, SU (KURVA S JURNAL MAHASISWA, 2014)
One of the fundamental factors to consider when offering road construction projects to the private sector is that the project must be financially viable. In a narrower context, keatraktivan usually measured from the NPV or IRR. Thus the issue of determining the discount rate or the minimum acceptable / attractive rate of return is the right to be one very crucial issue. This paper offers a methodology of calculation of Net Present Value (NPV) for the systematic construction of road infrastructure projects with a combined value of Internal Rate of Return (IRR).